STRATEGIES FOR REDUCING POST-WHITENING TOOTH SENSITIVITY (REMUNOM, 2024)
Teeth whitening is a highly sought-after cosmetic procedure to achieve a whiter smile. Despite its safety, dental sensitivity is a common side effect reported by patients. This occurs due to the penetration of peroxide into dental structures, causing discomfort. Various strategies have been studied to reduce this sensitivity, such as the use of desensitizing agents, laser, fluoride, potassium nitrate, and anti-inflammatories. Each strategy has its advantages and can be applied before or after whitening. Although there is no one hundred percent effective solution, professionals should select the best approach for each patient to minimize discomfort and maximize desirable and achievable aesthetic results.Keywords: Aesthetic; Teeth whitening; Sensitivity.